2020
DOI: 10.1021/acsami.0c18477
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Selective Printing of Gate Insulators Customized for Practical Application in Organic Integrated Devices

Abstract: Direct drawing techniques have contributed to the ease of patterning soft electronic materials, which are the building blocks of analog and digital integrated circuits. In parallel with the printing of semiconductors and electrodes, selective deposition of gate insulators (GI) is an equally important factor in simplifying the fabrication of integrated devices, such as NAND and NOR gates, and memory devices. This study demonstrates the fabrication of six types of printed GI layers (high/low-k polymer and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…In addition, it possesses high dielectric constant (≈13), and can diminish ferroelectric property, the character of PVDF‐HFP, by reducing its crystallinity, which leads to low voltage and hysteresis‐free TFT operation. [ 40 ] The combination of sCNT, FPVDF‐HFP, MXene makes it possible to fabricate high performance TFT and circuits with simple printing method. The EHD printing successfully produced continuous lines of MXene nanosheets and sCNT networks, as SEM images shown in Figure S13, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it possesses high dielectric constant (≈13), and can diminish ferroelectric property, the character of PVDF‐HFP, by reducing its crystallinity, which leads to low voltage and hysteresis‐free TFT operation. [ 40 ] The combination of sCNT, FPVDF‐HFP, MXene makes it possible to fabricate high performance TFT and circuits with simple printing method. The EHD printing successfully produced continuous lines of MXene nanosheets and sCNT networks, as SEM images shown in Figure S13, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…However, the voltage level of these logic gates was relatively high (~40 V), and this point can be a disturbing part for the industrialization of OFETs base PI layers. However, it can be improved if device geometry is improved, such as by applying short channel devices through photolithographic processes usually used in industry and high-k insulating materials that together can maintain high capacitance values [5,33]. Considering the results, this study showed the driving stability of OFETs with PI gate insulators, which were fabricated through factory methods.…”
Section: Resultsmentioning
confidence: 86%
“…Figure 2a shows AFM images of the prepared PI layers. The AFM image exhibited a smooth amorphous surface with a root-mean-square (RMS) roughness value of 0.212 nm, and this low RMS roughness value of less than 0.5 nm can provide a favorable environment for the growth of organic semiconducting crystals [5,19,20]. Furthermore, in order to identify the possibility of using this PI thin film as a dielectric layer for OFETs, the electrical characteristics were evaluated by fabricating a metal-insulator-metal (MIM)-structured capacitor with Al and thermally prepared PI layers (thickness: 150 nm) on Si/SiO 2 wafers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for integrating organic electronic circuits using bottom‐gate OFETs, a local coating and patterning of the gate dielectric layer are commonly required for fully covering the gate electrodes where input voltages are applied. [ 12 ] Therefore, a facile EHD technique should be exploited for the preparation of gate insulators (GIs) in low‐cost and large‐area circuit manufacturing.…”
Section: Introductionmentioning
confidence: 99%